ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Anita, Widya Febryari (Program Studi Akuntansi, Universitas Kuningan, 2017)
The goals of this research is to show the influence of liquidity, leverage, profitability, cash flow from operations, size, growth company, audit quality, audit lag, client tenure, debt default to the acceptance of going concern audit opinion at manufacture company listed on Indonesia Stock Exchange between 2010 to 2013. The population of this research are 148 manufacture companies. Sampling method that used in this research is purposive sampling, so I get 25 company samples to 4 years (2010-2013) with 100 analysis units by access the financial statement of auditee, independent audit report, and annual report on website www.idx.co.id. Analysis data technique that is used in this research is descriptive statistics analysis and logistic regression method. The results of this research indicate that. Leverage and audit lag has positive influence to the acceptance of going concern audit opinion. While other variable, cash flow from operations has negative influence to the acceptance of going concern audit opinion. Liquidity, profitability, size, growth company, audit quality, auditor client tenure, debt default has insignificantly influence to the acceptance of going concern audit opinion. Keywords: Liquidity, Leverage, Profitability, Cash Flow From Operation, Size, Growth Company, Audit Quality, Audit lag